Analisis Cemaran Bakteri Pada Teh Manis - Oktafirani Al As; Misika Alam; M. Ibnu Ubaidillah; Dina Anjani (Lembaga Pengembangan Kinerja Dosen, 2024)
Sweet tea drinks sold by street vendors are susceptible to contamination by bacteria. The presence of excess or pathogenic bacteria in sweet tea can cause health problems such as gastrointestinal infections, hence it is important to ensure sweet tea is free from bacterial contamination that is harmful to consumers' health. Penelitian ini bertujuan untuk mengetahui angka cemaran bakteri pada teh manis yang dijual oleh pedagang es teh manis di Kecamatan Plumbon Kabupaten Cirebon dan untuk mengetahui persentase teh manis yang tidak memenuhi syarat peraturan Badan POM RI No. 13 Tahun 2019 dalam parameter Angka Lempeng Total Bakteri dengan pemeriksaan pour plate (cawan tuang). This study used a survey research method. Sampling was done by total sampling. The samples of this study were 12 samples of sweet tea sold by sweet iced tea traders in Plumbon District, Cirebon Regency. Data analysis using percentages with simple calculations. Based on the results of the study, the highest bacterial contamination value was 16 × 105 colonies/mL and the lowest was 1.5 × 104 colonies/mL. Analysis of percentage data on 12 samples of sweet tea sold by sweet iced tea traders in Plumbon District, Cirebon Regency, 100% exceeded the threshold of the requirements of the Indonesian Food and Drug Administration Regulation No. 13 of 2019, making it unfit for consumption.